Using ionic liquid combined with HPLC-DAD to analyze semi-permanent hair dyes in commercial formulations - Franco, Jefferson Honorio [UNESP]; Silva, Bianca Ferreira da [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Royal Soc Chemistry, 2015)
Strict legislations in different countries have regulated the use of hair colorants and established the limits of dye concentration in cosmetics containing dyestuff. The present work describes a chromatographic HPLC-DAD method to determine the semi-permanent dyes basic blue 99 (BB99), acid violet 43 (AV43), basic brown 16 (BB16), basic red 76 (BR76) and basic yellow 57 (BY57) in hair coloring formulations. 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl) imide, BMIm[NTf2], an ionic liquid (IL) at room temperature, helped to improve the separation and quantification of low levels of basic and acidic dyes by HPLC coupled to a diode array detector. The developed method successfully identified the dyes in a commercial semi-permanent hair dyeing formulation and in drinking water. Comparison with an LC-MS/MS technique aided the validation of the results.